Set me free - LeZotte, Ann Clare (LeZotte, Ann Clare. Show me a sign trilogy, 2021)
Mary Lambert still hasn't fully recovered from her ordeal of being a "live specimen" for Dr. Andrew Noble to study. Now, her life back on Martha's Vineyard isn't what it once was. So when an old acquaintance asks her to come to the mainland and teach a young deaf girl to communicate, Mary reluctantly agrees. She is unsure if she is up to the job of teaching a girl with no prior language but soon after arriving, Mary learns the girl's predicament is shocking and horrific in ways that she never expected.